Chest MRI as an emerging modality in the evaluation of empyema in children with specific indications: Pilot study. Issue 8 (19th May 2021) - Sodhi, Kushaljit S.; Bhatia, Anmol; Nichat, Vaibhav; Mathew, Joseph L.; Saxena, Akshay K.; Samujh, Ram; Singh, Meenu
Abstract: Objectives: To assess the diagnostic role of chest magnetic resonance imaging (MRI) for evaluating empyema in children with specific indications. Methods: Nineteen children (5–16 years) with a diagnosis of empyema were enrolled in this prospective study from January 2018 to February 2020. MRI and multidetector computed tomography (MDCT) of the chest was performed within 48 h of each other. Two pediatric radiologists independently evaluated the MRI and CT images for the presence of fluid and air in the pleural cavity, septations within the fluid, pleural thickening, pleural enhancement, drainage tube tip localization, consolidation, and lymphadenopathy. Kappa test of agreement was used to determine the agreement between the MRI and MDCT findings. Chance‐corrected kappa statistics were used for calculating the interobserver variation. Results: The kappa test showed almost perfect agreement ( κ = 1) between MRI and MDCT for detecting fluid, pleural thickening, pleural enhancement, drainage tube tip localization, consolidation, and lymphadenopathy. Septations within the fluid were detected in 16 (84.2%) patients on MRI, and in 14 (73.7%) patients on MDCT. Almost perfect agreement ( κ = 0.81–1.00) was seen for all the findings on CT and MRI between the two radiologists, except for pleural thickening for which a strong agreement ( κ = 0.642) was observed. Conclusion: MRI is comparable to MDCT for the detection of various findings in children with empyema. MRI may be considered in lieu of CT, as a problem‐solving tool and as a radiation‐reducing endeavor in children with empyema, specifically, only where CT is required for preoperative planning and evaluation of complications.